In the picture : the facts behind the fiction in Evelyn Waugh's Sword of Honour - Gallagher, Donat (Costerus, 2014)
Evelyn Waugh at war is an irresistibly fascinating subject, as are his war novels and diaries. Drawn to units offering the greatest danger, but often frustrated in his search for action, Waugh served in multiple regiments, saw battle on Crete and worked behind the lines in occupied Croatia. In the Picture traces Waugh's experiences, both vivid and mundane, with a completeness never before attempted and shows how they come alive in Sword of Honour. It also illuminates the brief hints within the narrative of key events of the war, while highlighting its strategic direction. Waugh's individualist.